Establishment of a Real-Time Recombinase Polymerase Amplification Assay for the Detection of Avian Reovirus - Ma, Lei; Shi, Hongfei; Zhang, Mingliang; Song, Yuwei; Zhang, Kunpeng; Cong, Feng (Frontiers in Veterinary Science, 2020)
Avian reovirus (ARV) infection results in multiple disease manifestations in chicken. A rapid detection method will contribute to early diagnosis and control of the virus infection. The recombinase polymerase amplification (RPA) technology is a nucleic acid amplification method which is experiencing rapid development. In present study, a real-time reverse transcription (RT)-RPA assay was developed for the detection of ARV. The limit of detection of the real-time RT-RPA was 102 copies/μL of ARV genomic RNA standard in 95% of cases. The RT-RPA assay also exhibited remarkable specificity. When the nucleic acids of CRV and other common avian pathogens were subjected to the RT-RPA test, only ARV tested positive, all the other pathogens tested negative. Furthermore, the practicality of the RT-RPA assay in field was confirmed by testing 86 clinical samples. The clinical samples were also detected by qRT-PCR. The detection result by RT-RPA was 96.5% agreement with that of qRT-PCR. As a result of the simplicity and convenience of the assay with high sensitivity and specificity, the probe-based RT-RPA will be an alternative diagnostic assay for the detection of ARV in resource-limited settings.